The socialization of a badminton Shuttle Time for the educative education and elementary school level in Padang Utara - zarwan zarwan; Sefri Hardiansyah; Ade Zalindro (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2019)
The problems in this activity are many teachers who still use the methods of training in the learning process of physical education of sports and Health (PJOK) especially badminton so that students do not experience improvement in the game Badminton. The purpose of this activity is to improve the teacher's ability to study badminton through shuttle time. The objective of the event is PJOK teacher in Padang Utara Sub-district with 26 people. To measure the success of this activity was given a question as much as 50 rounds before and after activities. From the question obtained initial data access is 750 (57.69) and the final data 1061 (81.62%) An increase of 23.93%.